2019
DOI: 10.1039/c9ra04135d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electrocatalytic reduction of carbon dioxide by metal-doped β12-borophene monolayers

Abstract: These new TM–Bβ12 monolayers will display excellent catalytic performance for electroreduction of CO2. Primary reduction product of Sc is CO (overpotential 0.45 V). Primary product Ti–Zn is CH4, and Fe–Bβ12 has 0.45 V overpotential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…As a comparison, Cu particles (10-50 nm) supported on Ti 3 C 2 T x (denoted as Cu-NP/Ti 3 C 2 T x ; Supplementary Figs. [26][27][28][29][30] were also prepared with a Cu loading of 5.2 wt%. Cu-NP/Ti 3 C 2 T x shows a very low current density of -16.2 mA cm −2 at -1.0 V vs RHE ( Fig.…”
Section: Synthesis and Characterization Of Cu-sa/ti 3 C 2 Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparison, Cu particles (10-50 nm) supported on Ti 3 C 2 T x (denoted as Cu-NP/Ti 3 C 2 T x ; Supplementary Figs. [26][27][28][29][30] were also prepared with a Cu loading of 5.2 wt%. Cu-NP/Ti 3 C 2 T x shows a very low current density of -16.2 mA cm −2 at -1.0 V vs RHE ( Fig.…”
Section: Synthesis and Characterization Of Cu-sa/ti 3 C 2 Tmentioning
confidence: 99%
“…Recently, the two-dimensional (2D) materials, as a powerful platform to support SA catalysts, have attracted great attention because of large specific surface areas, more exposed active sites, and superior catalytic activities [24][25][26][27][28][29][30] . Particularly, with excellent electronic conductivity, catalytically active basal planes, and graphene-like unique layered structures, 2D Ti 3 C 2 T x MXene (T x represents surface functional groups) has been investigated extensively for a variety of electrochemical reactions [31][32][33] .…”
mentioning
confidence: 99%
“…1,2 In recent years, various catalysts, such as nanoparticle supported catalysts and single site catalysts, have been designed and used in diverse chemical reactions. [3][4][5][6][7][8][9][10][11][12][13][14][15] Palladium and gold supported nanoparticle catalysts have been intensively investigated and extensively used in the selective BD hydrogenation because of their superior catalytic activity and selectivity. [14][15][16][17] Previous studies on supported Pd-based nanoparticle catalysts have revealed that they have superior catalytic activity in the selective BD hydrogenation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Due to their high specic surface area, reduced dimensionality and remarkable properties, two-dimensional (2D) nanosheets have become an ideal platform for the design of novel electrocatalysts for CO 2 reduction. [20][21][22][23][24][25][26][27] Borophene is a novel 2D material under active investigation due to its fascinating and diverse properties and potential. 28 The properties of borophene can be enhanced and extended by alloying with other elements.…”
Section: Introductionmentioning
confidence: 99%